Persistent Cryptococcal Brain Infection despite Prolonged Immunorecovery in an HIV-Positive Patient - Tom Wingfield; Jo Baxter; Amit Herwadkar; Daniel du Plessis; Tom J. Blanchard; F. Javier Vilar; Anoop Varma (Case Reports in Neurological Medicine)
Background. HIV-positive people starting combined antiretroviral therapy may develop immune reconstitution to latent or treated opportunistic infections. Immune reconstitution to cerebral Cryptococcus is poorly understood and can be fatal. Case Presentation. A 33-year-old Zimbabwean female presented with cryptococcal meningitis and newly diagnosed HIV with a CD4 count of 51 cells/μL (4%). She was treated with amphotericin and flucytosine. Combined antiretroviral therapy was started four weeks later and she showed early improvement. However, over the ensuing 18 months, her clinical course was marked by periodic worsening with symptoms resembling cryptococcal meningitis despite having achieved CD4 counts ≥400 cells/μL. Although initially treated for relapsing cryptococcal immune reconstitution syndrome, a brain biopsy taken 17 months after initial presentation showed budding Cryptococci. Conclusion. This unusually protracted case highlights the difficulties in differentiating relapsing cryptococcal meningitis from immune reconstitution and raises questions concerning the optimum timing of initiation of combined antiretroviral therapy in such patients.